Cognitive dysfunction in diabetes – the ‘forgotten’ diabetes complication: a narrative review - Åke Sjöholm; Louise Bennet; Peter M. Nilsson (Scandinavian Journal of Primary Health Care)
Background In addition to peripheral neuropathy of various kinds, diabetes can also cause central neuropathy, which among other things can manifest itself as premature cognitive dysfunction, often linked to vascular dysfunction. Although the link between diabetes and cognitive dysfunction was discovered more than 100 years ago and has important clinical implications, this diabetes complication remains relatively unknown. Recent years have seen research that has clarified cerebral insulin resistance and defective insulin signaling as examples of pathogenic factors behind this cognitive impairment in diabetes.Method We provide a narrative review of select and contemporary publications with relevance for the interface between diabetes/prediabetes and cognitive function.Results Recently published studies show that physical activity can reverse insulin resistance in the brain as well as cognitive impairment and pathological appetite regulation. Pharmacological interventions with, for example, nasal insulin, GLP-1 receptor agonists, SGLT-2 inhibitors, or PPAR-γ agonists have also shown promising results.Conclusion Optimization of lifestyle factors (e.g. physical activity), as well as several pharmaceutical agents already in clinical use against diabetes, have shown promising results in improving cognitive function in diabetic patients. An important task for primary health care, where most patients with type 2 diabetes are diagnosed, treated, and followed, is to increase awareness and early detection of cognitive dysfunction in these patients for optimizing risk factor control.